The GIMAP Family Proteins: An Incomplete Puzzle - Limoges, Marc-André; Cloutier, Maryse; Nandi, Madhuparna; Ilangumaran, Subburaj; Ramanathan, Sheela (Frontiers in Immunology, 2021)
Long-term survival of T lymphocytes in quiescent state is essential to maintain their cell numbers in secondary lymphoid organs and in peripheral circulation. In the BioBreeding diabetes-prone strain of rats (BB-DP), loss of functional GIMAP5 (GTPase of the immune associated nucleotide binding protein 5) results in profound peripheral T lymphopenia. This discovery heralded the identification of a new family of proteins initially called Immune-associated nucleotide binding protein (IAN) family. In this review we will use ‘GIMAP’ to refer to this family of proteins. Recent studies suggest that GIMAP proteins may interact with each other and also be involved in the movement of the cellular cargo along the cytoskeletal network. Here we will summarize the current knowledge on the characteristics and functions of GIMAP family of proteins.